If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2(x+3)=2x-(4-x)-12
We simplify the equation to the form, which is simple to understand
1/2(x+3)=2x-(4-x)-12
Reorder the terms in parentheses
+( + 0.5x+1.5)=2x-(4-x)-12
Remove unnecessary parentheses
+ 0.5x+1.5=+2x-(+4-x+)-12
Remove unnecessary parentheses
+ 0.5x+1.5=2x-4+1x-12
We move all terms containing x to the left and all other terms to the right.
+ 0.5x-2x-1x=-4-12-1.5
We simplify left and right side of the equation.
-2.5x=-17.5
We divide both sides of the equation by -2.5 to get x.
x=7
| -20=-4n+10 | | -6(u+6)=-9u-15 | | 16x-5/17-15x | | 7v^2-78v+80=0 | | ln(x+6)+ln(x)=1 | | A=(4x+1)(x+1) | | X*-9=-81 | | 4/7y-2=3/7y | | 1/2(7x-5)-6x+2=0 | | -5x-26=-2(x+4) | | 2+4-5-7x= | | 1/4m-2=-10 | | 6x-y=2200 | | 6(x+4)=40 | | 7v^2-8v+80=0 | | 5x+2x-4=31 | | 2x+(0)=-5 | | (2x-3)(2x+3)=15x-5 | | 5(u+7)=8u+41 | | 5(4+8x)=-29 | | -5(8+4a)=14+7a | | 17-2x=44 | | 3/4-d1/4 | | 5(x+1)(x-1)+1=4x^2 | | 20-yi=2x+6i | | 7x+10=x+16 | | 5-s/9-s=4/s-9 | | log(8)(x-3)+log(8)(x+4)=1 | | 9x+4=2x+33 | | 6b^2-20b=0 | | 6(x+4)=28 | | 4x+60=140-2x |